Feedlot of lambs fed biodiesel co-products: performance, commercial cuts and economic evaluation - Romanzini, Eliéder Prates [UNESP]; da Silva Sobrinho, Américo Garcia [UNESP]; de Lima Valença, Roberta [UNESP]; Borghi, Thiago Henrique [UNESP]; de Andrade, Nomaiací [UNESP]; Bernardes, Priscila Arrigucci [UNESP] (Springer Nature, 2018)
The aim of this study was to evaluate the animal performance, commercial cuts, and their yields within the production system, and economics of sheep production, of lambs finished in feedlots and fed with or without biodiesel co-products. A total of 40 lambs were divided into four biodiesel co-product treatment groups: a no-treatment control; peanut meal; crude glycerin; and peanut meal + crude glycerin. Animal performance did not differ (P > 0.05) among the treatment groups, where the average daily gain was close to 0.26 kg/day. Likewise, the quantitative carcass characteristics did not differ (P > 0.05) and the biological mean yield was 54.92%. Similarly, the commercial cuts and their yields did not differ (P ≥ 0.09) among the treatments. These results took into consideration the standard, age, and slaughter body weight of the animals. The economic evaluation determined that peanut meal was the best co-product for use in finishing lambs in a feedlot. Hence, all the biodiesel co-products evaluated can be used at feedlots to finish lambs without changing the variables measured.
Keywords: Crude glycerin; Partial budgets; Peanut meal